EFEKTIVITAS PROGRAM PENYULUHAN PERTANIAN DALAM MENDORONG PRAKTIK PERTANIAN BERWAWASAN LINGKUNGAN: STUDI KASUS DI KECAMATAN SAWANGAN, KABUPATEN MAGELANG - Atmiyati, Sri Utami; Hermawati, Istiana (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2025)
Environmentally sound agriculture is a strategic approach to address land degradation due to conventional chemical-based farming practices. This study aims to evaluate the effectiveness of extension programs in encouraging the adoption of environmentally friendly agricultural practices in Sawangan District. Using a qualitative descriptive method, data was obtained through in-depth interviews with eight agricultural extension workers and several assisted farmers. The results showed that although the extension was well received, the limited capacity of extension workers, the lack of support for sustainable programs, and the resistance of farmers hindered the effectiveness of the extension. This study emphasizes the importance of increasing the capacity of extension workers, innovating extension methods based on active participation, and integrating information technology approaches in extension services. Strategic recommendations are given to strengthen the effectiveness of extension in supporting sustainable agriculture. ABSTRAKPertanian berwawasan lingkungan merupakan pendekatan strategis untuk mengatasi degradasi lahan akibat praktik pertanian konvensional berbasis bahan kimia. Penelitian ini bertujuan mengevaluasi efektivitas program penyuluhan dalam mendorong adopsi praktik pertanian ramah lingkungan di Kecamatan Sawangan. Menggunakan metode deskriptif kualitatif, data diperoleh melalui wawancara mendalam dengan delapan penyuluh pertanian dan sejumlah petani binaan. Hasil menunjukkan bahwa meskipun penyuluhan diterima dengan baik, keterbatasan kapasitas penyuluh, kurangnya dukungan program berkelanjutan, dan resistensi petani menghambat efektivitas penyuluhan. Penelitian ini menekankan pentingnya peningkatan kapasitas penyuluh, inovasi metode penyuluhan berbasis partisipasi aktif, serta integrasi pendekatan teknologi informasi dalam pelayanan penyuluhan. Rekomendasi strategis diberikan untuk memperkuat efektivitas penyuluhan dalam mendukung pertanian berkelanjutan